Effect of Wheat Straw Ash on Fresh and Hardened Concrete Reinforced with Jute Fiber - Bheel, N. (Hindawi Limited, 2021)
In the present era, a number of researchers are using either industrial or agricultural priceless products as a basic source of raw materials for the construction industry. These waste products are economical and helpful in producing a sustainable environment and reducing environmental pollution, which is called handling waste products. However, this research work was conducted on concrete containing 0.25, 0.50, 0.75, and 1 of jute fiber as reinforcement material and 10, 20, 30, and 40 of wheat straw ash (WSA) as replacement for fine aggregates. Moreover, the separate and combined effect of jute fiber and WSA as a replacement for sand ingredient in concrete is to determine the fresh and hardened properties of concrete. In this research, a number of concrete samples were prepared with 1: 1.5: 3 mix proportion at 0.54 water-cement ratio and cured at 28 days. The experimental outcomes displayed that the compressive, splitting tensile, and flexural strengths improved by 32.88 MPa, 3.80 MPa, and 5.30 MPa at 0.50 of jute fiber along with 30 of WSA at 28 days consistently. Similarly, the modulus of elasticity was developed while the dosages of jute fiber and WSA increased together in concrete. Moreover, the permeability and workability of concrete were reduced while utilized jute fiber and WSA increased together in concrete. Â© 2021 Naraindas Bheel et al.